Analisa Sistem Back-Up Daya Airfield Lighting System pada Substation T1 Bandara SAMS Sepinggan dengan ETAP 19.0.1 - Tjung, Aldi Wiradinata Bukhari; Marzuki, Marza Ihsan; Yulianto, Bayu Yustina (Jambura Journal of Electrical and Electronics Engineering, 2024)
Dalam menunjang keselamatan penerbangan digunakan alat bantu dalam proses lepas landas, landing, dan taxi di bandara seperti Air Traffic Controller (ATC) dan Airfield Lighting System (AFL). Alat bantu tersebut pada Bandara SAMS Sepinggan dipasok dengan kapasitas listrik sebesar 3465 KVA pada Main Power House 1 yang disuplai dari PLTU Kariangau Balikpapan. Dalam menunjang operasional, Bandara SAMS Sepinggan tidak hanya mengandalkan sumber daya listrik primer dari PLN saja, ketika sumber PLN mengalami pemadaman maka sumber daya listrik sekunder berperan yaitu genset dan Uninterruptible Power Supply (UPS) sebagai catu daya cadangan tidak terputus khususnya pada beban AFL. Suplai daya listrik sekunder pada Bandara SAMS harus dapat membangkitkan daya sebesar 94.33 KVA untuk beban AFL. Metode load flow analysis digunakan untuk Analisa sistem back-up daya menggunakan program ETAP (Electric Transient Analysis Program) dengan tiga skenario. Setiap skenario disesuaikan dengan kondisi yang dimungkinkan terjadi ketika terjadi pemadaman. Skenario paling kritis yaitu skenario menggunakan suplai dari UPS dimana genset belum siap karena satu atau lain hal. Genset dapat membangkitkan daya sebesar 84.2 KW untuk mengisi daya UPS dan melayani beban sebesar 94.33 KVA. Kondisi drop tegangan pada saat suplai dari genset ketika PLN padam dalam kondisi baik dimana 98% berdasarkan standar IEC.To support aviation safety, tools are used in the take-off, landing and taxi processes at airports such as the Air Traffic Controller (ATC) and the Airfield Lighting System (AFL). The auxiliary equipment at SAMS Sepinggan Airport is supplied with an electricity capacity of 3465 kVA at Main Power House 1 which is supplied from PLTU Kariangau Balikpapan. In supporting operations, SAMS Sepinggan Airport does not only rely on primary electricity resources from PLN, when PLN sources experience a blackout, secondary electrical resources play a role, namely generators and Uninterruptible Power Supply (UPS) as uninterruptible backup power supplies, especially for AFL loads. Research on Analysis of the Back-Up Power System for the Airfield Lighting System at Substation T1 at SAMS Sepinggan Airport with ETAP 19.0.1 aims to see a picture of the distribution system when secondary electrical resources operate when there is a blackout at the source from PLN by looking at the effects that occur on the system. The method used in this research is an experiment with a simulation approach using the ETAP (Electric Transient Analysis Program) program. In the simulation carried out, there were three scenarios. Each scenario is adapted to the conditions that may occur when a blackout occurs. The most critical scenario is the scenario using supply from UPS where the generator is not ready for one reason or another. The generator can generate 84.2 kW of power to charge the UPS and serve a load of 94.33 kVA. The voltage drop condition at the time of supply from the generator when PLN is turned off is in good condition, which is 98% based on IEC standards, namely the lowest is 98.09% or 372 V based on IEC standards.